Pengaruh Budaya Organisasi, Lingkungan Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Muhammad Rifki (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of organizational culture, work environment, and work discipline on employee performance with job satisfaction as a mediating variable. This research is motivated by the increasing demands on organizations to achieve optimal employee performance amid intense competition and increasingly dynamic changes in the work environment. Employee performance is a key factor in determining organizational success; therefore, it must be supported by a strong organizational culture, a conducive work environment, and good work discipline. In addition, job satisfaction is considered an important psychological factor that can strengthen the relationship between these factors and employee performance. This study employs a quantitative approach using a survey method. The population of this research consists of all employees at the company that serves as the research object. The sampling technique used is saturated sampling or purposive sampling, based on the consideration that respondents meet the criteria relevant to the research objectives. Research data were collected through the distribution of questionnaires to respondents, which were developed based on indicators of each research variable and measured using a Likert scale. The independent variables in this study include organizational culture, work environment, and work discipline, while the dependent variable is employee performance and the mediating variable is job satisfaction. The collected data were analyzed using statistical analysis techniques with the assistance of SPSS software. The stages of data analysis include validity testing and reliability testing to ensure the feasibility of the research instruments, classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression analysis to examine the effect of independent variables on the dependent variable. In addition, this study applies the coefficient of determination (R²) to determine the ability of independent variables to explain variations in the dependent variable and uses the Sobel test to examine the role of job satisfaction as a mediating variable. The results show that organizational culture, work environment, and work discipline have a positive and significant effect on employee job satisfaction. These findings indicate that a strong organizational culture, a comfortable and supportive work environment, and a high level of work discipline are able to increase employees’ job satisfaction. Furthermore, the results also show that organizational culture, work environment, and work discipline have a positive and significant effect on employee performance. Job satisfaction is proven to have a positive and significant effect on employee performance and is able to significantly mediate the influence of organizational culture, work environment, and work discipline on employee performance. This study is expected to provide a theoretical contribution to the development of human resource management studies, particularly those related to employee performance and the role of job satisfaction as a mediating variable. Practically, the results of this study are expected to serve as a consideration for company management in formulating policies oriented toward strengthening organizational culture, creating a conducive work environment, improving work discipline, and managing employee job satisfaction sustainably in order to enhance employee performance and achieve organizational goals.